Aligning Sustainability Integration, Digitalization and Inclusivity for Green, Sustainable Recovery - Aassouli, Dalal; Shah, Mohamed Eskandar (PT Penjaminan Infrastruktur Indonesia (Persero), 2022)
This article provides a roadmap for sustainable recovery that can aid policymakers in implementing sustainable recovery and improving the well-being of people. The roadmap will prioritize three areas of action: sustainability, digitalization, and inclusivity. This article emphasizes the involvement of the private sector and innovative financing solutions (including Islamic finance) in meeting the financing gap for investment in relevant infrastructure for all three pillars. This articles demonstrates that financial innovation, investment in green and social projects, market awareness, and synergies among the various sustainable finance segments will form the foundation for long-term recovery and create a vibrant and resilient economy.